DISTRIBUTION OF HEALTH FACILITY SERVING CATARACT SURGERY IN SOUTH SULAWESI - ARIFFIN, ANNISA IKHSANIAH; Amalius, Ahmad ashraf; Faisal, Andi Akhmad; Kamaruddin, Muhammad Irfan (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesOne of the elements in Vision 2020: the right to sight is the fulfillment of resources to reduceavoidable blindness. According to the Indonesian’s prevention of blindness roadmap about sources,we need to collect the data about health facilities serving cataract surgery. The aim of this study isto provide the data about health facilities serving cataract surgery in South Sulawesi Province. MethodsA descriptive study using a questionnaire which is distributed to hospitals/clinics in South SulawesiProvince. In addition, secondary data was also used from previous research conducted by one of theresidents of Ophthalmology at Hasanuddin University. All the data were collected from Januari toJune 2022. ResultsThe distribution of health facilities in all districts/cities in South Sulawesi has at least one healthfacility serving cataract surgery, with the most distribution in Makassar. Twelve of 62 hospitals andfive of 27 eye clinics have not provided cataract surgery services..There are 6 districts (25%) thathave not fullfil the minimum number standard of ophthalmologist according to WHO. Alldistrict/cities in the Province have all the instrument required for cataract surgery. ConclusionEvery district/city in South Sulawesi has at least one health facility serving cataract surgery.Information on the distribution of health facilities serving cataract surgery needs to be routinelyconducted twice a year according to Indonesian’s prevention of blindness roadmap.